A Mini-Review of the Role of Glutamate Transporter in Drug Addiction - Wang, Wenjun; Zeng, Fancai; Hu, Yingying; Li, Xiang (Frontiers in Neurology, 2019)
The development of new treatment for drug abuse requires identification of targetable molecular mechanisms. The pathology of glutamate neurotransmission system in the brain reward circuit is related to the relapse of multiple drugs. Glutamate transporter regulates glutamate signaling by removing excess glutamate from the synapse. The aim of this review is to highlight the effects of drug addiction on glutamate transporter and glutamate uptake, and targeting glutamate transporter as an addictive drug addiction treatment.